The Effect of Training on the Performance of Civil Servant Teachers in Cluster 04, Alak District, Kupang City - Djewa Raga, Amelia; Djami, Reysanti; Sayd, A. Imelda; Noach, Robert (Journal of Practical Management Studies, 2024)
This research aims to determine the effect of training on the performance of civil servant teachers in cluster 04, Alak sub-district, Kupang City. The formulation of the problem put forward is whether training influences the performance of civil servant teachers in Cluster 04, Alak District, Kupang City. This type of research is referred to as survey research, namely research that takes samples from a population and uses questionnaires as the main data collection tool (Sugiyono, 2013: 39). The population in this study were all civil servant teachers in Cluster 04, Alak District, Kupang City, and the sample taken was 44 teachers using the Saturated Sampling Technique. The data collection techniques in this research are observation, interviews, questionnaires and literature, while the data analysis technique is using descriptive statistical methods. The research results show that there is a strong relationship with a value of 0.541 and is significant between training and performance. From the data analysis it was concluded that the training variable had an influence of 29.2% on the performance variable, while the remaining 70.8% was contributed by other variables not included in the model (not researched).